Analysis of learning models for children with disabilities in inclusive education in primary schools - Cesil Putri Ariyunda; Utama, Candra (JPI (Jurnal Pendidikan Inklusi), 2024)
Inclusive education is important to incorporate students with special needs in an equal learning environment, although there are still challenges in providing effective education services. This study aims to analyze appropriate learning models for children with disabilities in the context of inclusive education in primary schools. The method used was descriptive qualitative, with the research subjects consisting of teachers and students in primary schools. The results showed that the application of the classical learning model and special guidance has a positive impact on the learning process of children with disabilities, with adjustments to learning strategies and materials that suit their needs. Data were analyzed through observation, interviews and document analysis, which showed the importance of collaboration between teachers, parents and other related parties in supporting the success of inclusive education. The success of the inclusive learning model depends on the model that is implemented and the support from various parties to create an inclusive learning environment. support from various parties to create an adaptive and efficient learning environment for all students.